2018
DOI: 10.1038/s41598-018-35969-1
|View full text |Cite
|
Sign up to set email alerts
|

Chemosynthesis and characterization of site-specific N-terminally PEGylated Alpha-momorcharin as apotential agent

Abstract: Alpha-momorcharin (α-MC), a type I ribosome-inactivating protein (RIP) isolated from Momordica charantia seeds, has been extensively studied for its antitumor, antiviral and antifungal activities. However, as an exogenous protein, problems associated with short half-life and strong immunogenicity have limited its clinical application. Poly (ethylene glycol) (PEG), as a polyether compound, is a well established and efficient modifier to develop it as a potential agent. Nevertheless, conventional PEGylation is n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…While lethal to mammalian cells, RIPs can also display antiviral features [8] and can inhibit animal and plant viruses such as HIV‐1, [9] poliovirus [10] and tobacco etch virus [11] . RIP‐conjugated toxins have also been developed as potential antitumor agents [12,13] . Their unique and surgically directed cellular activity, as well as potency and potential utility as biowarfare agents, have therefore attracted considerable interest over the years, [14] aiming particularly at the development of effective strategies for real time activity monitoring and detection [15] …”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…While lethal to mammalian cells, RIPs can also display antiviral features [8] and can inhibit animal and plant viruses such as HIV‐1, [9] poliovirus [10] and tobacco etch virus [11] . RIP‐conjugated toxins have also been developed as potential antitumor agents [12,13] . Their unique and surgically directed cellular activity, as well as potency and potential utility as biowarfare agents, have therefore attracted considerable interest over the years, [14] aiming particularly at the development of effective strategies for real time activity monitoring and detection [15] …”
Section: Figurementioning
confidence: 99%
“…[11] RIP-conjugated toxins have also been developed as potential antitumor agents. [12,13] Their unique and surgically directed cellular activity, as well as potency and potential utility as biowarfare agents, have therefore attracted considerable interest over the years, [14] aiming particularly at the development of effective strategies for real time activity monitoring and detection. [15] Prior studies have utilized enzyme-linked immunosorbent assay (ELISA), [16] immuno-PCR [17] and mass spectrometry to assess RIP activity.…”
mentioning
confidence: 99%
“…Mono-, di-, tri-PEGlyated α-MMC and MAP30 dramatically reduced the immunogenicity and maintained biological activities [112,113]. The enzymatic activity assay showed that mono-PEGylated α-MMC strongly inhibited the growth of human cervix adenocarcinoma cells [116]. Sun et al provided a method to isolate high purity mono-mPEGylated MAP30 and α-MMC, which can be useful for further RIP drug examination [111].…”
Section: Coupling With Polymer Polyethylene Glycerol (Peg) and Dextranmentioning
confidence: 99%
“…Mono-, di-, tri-PEGlyated α-MMC and MAP30 dramatically reduced the immunogenicity and maintained biological activities [112,113]. The enzymatic activity assay showed that mono-PEGylated α-MMC strongly inhibited the growth of human cervix adenocarcinoma cells [116]. Sun et al provided a method to isolate high purity mono-mPEGylated MAP30 and α-MMC, which can be useful for further RIP drug examination [111].…”
Section: Coupling With Polymer Polyethylene Glycerol (Peg) and Dextranmentioning
confidence: 99%
“…The plasma half-life of α-MMC was sharply increased from 6.2-7.5 h to 52-87 h [114]. The homogeneity of PEGlyated α-MMC was further improved by site-specific conjugation of mPEG-ALD [116]. Due to steric hindrance of active sites, PEGylation may lead to biological activity reduction, which can be compensated by longer plasma half-life [119].…”
Section: Coupling With Polymer Polyethylene Glycerol (Peg) and Dextranmentioning
confidence: 99%